A Using Text Evaluator to Analyze Reading Texts in Indonesian Grade X English Course Book - Hidayat, Hamdan (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
Selecting the appropriate text for reading material is important to be considered by an English teacher. The text should be evaluated for its complexity before being used in reading class. If the text is too difficult the students may be intimidated and if the text is too easy the students may be bored and be unmotivated. This issue is rarely touched by the teacher in Indonesia. This paper examines the use of TextEvaluator to analyze the reading material in Senior High School English Course Book Grade X. There are thirteen texts found in the book, and all of them were analyzed. The result reveals that only two texts are appropriate to Grade X. One text is above Grade X and ten texts are below Grade X.